Five-Year Survival of Children With Chronic Critical Illness in Australia and New Zealand. Issue 4 (August 2016) - Namachivayam, Siva P.; Alexander, Janet; Slater, Anthony; Millar, Johnny; Erickson, Simon; Tibballs, James; Festa, Marino; Ganu, Subodh; Segedin, Liz; Schlapbach, Luregn J.; Williams, Gary; Shann, Frank; et al.
Abstract : (Abstracted from Crit Care Med, 43:1978–1985, 2015) The long-term survival of children with chronic critical illnesses, such as liver insufficiency and acute renal failure, is understudied. Researchers conducted this study as a means to discover crucial information regarding survival rates in chronically ill children 16 years and younger.